(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines how human speech allows us to distinguish abstract concepts from material things. Words provide a clear picture of these concepts, making them understandable to both the speaker and others. Speech helps us think more clearly and develop complex ideas.